FEDERAL BUDGET 2016 AS AN INDICATOR OF STATE ECONOMIC POLICY: DRIFT OR DEVELOPMENT? - Vladimir A. Slepov; Alla Yu. Chalova; Stanislav A. Baranovskiy (Вестник Российского экономического университета имени Г. В. Плеханова, 2017)
The article provides a critical assessment of the current structure of the federal budget in conditions of passive economic policy in Russia. Problematic aspects of the draft federal budget 2016 were analyzed in the context of growing adverse trends in Russian economy. Special attention was paid to the assessment of the new format of the draft federal budget 2016, its balancing in conditions of cyclic slump and recommendations aimed at intensifying anti-recession impact of the federal budget on Russian economy. The interconnection of the federal budget and economic policy being pursued in Russia was substantiated and the necessity to revise expenses to raise anti-crisis impact on economy was shown. The authors advanced a methodological approach to estimate the influence of concrete budget expenses on GDP through fiscal multipliers for the period of one, three and five years. Recommendations were offered on structuring budget expenses by the duration of their economic effects and role in stimulating economic activity.